PENGARUH PERTUMBUHAN PERUSAHAAN DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN DI INDONESIA - Kencana, Angelica Putri; Chandra, Santoso (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The purpose of this research is to obtain empirical evidence on influence of asset growth and other factors on firm value in Indonesia. This research has seven independent variables, namely profitability, capital structure, firm size, asset growth, dividend policy, liquidity, and sales growth. This research used a sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2021 to 2023, with 132 data from 44 companies. This research uses a purposive sampling method for sample selection and multiple regression for data analysis. The results of this research indicate that profitability, capital structure, and liquidity have an effect on firm value. Meanwhile, other independent variables such as company size, asset growth, dividend policy, and sales growth do not affect on firm value.